Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus Online Requisition (ORAS) Pada PT Freeport Indonesia) - Nazva Abiya; Nanang Yudi Setiawan; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Freeport Indonesia is an affiliate company of Freeport-McMoRan, which engaged in mining. In the procurement of company goods, PT Freeport Indonesia has a process called ORAS. ORAS or Online Requisition is a custom application to facilitate the requisition and reservation process from a material in PT Freeport Indonesia warehouse. But there are problems in the process of ordering goods in the reservation or requisition such as, input the wrong cost code allocation by employees that are not in accordance with the appropriate departments, late buyers in taking goods in warehouses and other problems that can be found if the evaluation is done. Therefore, is necessary to analyze and evaluate to find out the problems that exist in the current business process and the improvement of business processes based on the results of the evaluation. Failure Mode and Effect Analysis (FMEA) is used to evaluate business process, then recommendations for improving business processes using the Business Process Improvement (BPI) method with streamlining tool. The duration of completion is faster up to 11.21% for reservation business processes and 4.87% for the Requisition business process. The duration of completion is slower up to 30.38% in the ordering business process at ORAS and 20.24% in the Bid Requisition business process.